A configurational analysis of IT governance: A study of the financial services sector in Ghana. Issue 1 (13th August 2022) - Asmah, Alexander; Kyobe, Michael
Abstract: This study seeks to answer the question, what is the right configuration of IT Governance mechanisms that will improve performance? Although few studies have addressed how governance mechanisms improve performance, these studies have adopted a linear approach in assessing the relationships among governance mechanisms. The nature of the linear relationships has not answered the lingering question making this study crucial. The study follows the configurational theories that for IT governance to improve performance, all the governance mechanisms much be implemented coherently. We used Cluster analysis to assess the nature of the configuration in the Ghanaian Financial Services Sector using 7 companies. Our findings confirm our theory that to improve performance, IT Governance mechanisms must be implemented coherently. However, in a fast‐changing environment, there is the need to increase focus on technological mechanisms to provide timely information for decision making, collaboration and reduce information asymmetry. As a contribution to practice, this study recommends that policy makers in the financial space should emphasize the need for adequate IT Governance implementations with the right configuration. Companies in the pension and savings and loan sectors should be encouraged to adopt more technological mechanisms.